Determination of jet energy calibration and transverse momentum resolution in CMS - Chatrchyan, S. (2011)
Measurements of the jet energy calibration and transverse momentum resolution in CMS are presented, performed with a data sample collected in proton-proton collisions at a centre-of-mass energy of 7TeV, corresponding to an integrated luminosity of 36p(-1). The transverse momentum balance in dijet and gamma/Z+jets events is used to measure the jet energy response in the CMS detector, as well as the transverse momentum resolution. The results are presented for three different methods to reconstruct jets: a calorimeter-based approach, the Jet-Plus-Track approach, which improves the measurement of calorimeter jets by exploiting the associated tracks, and the Particle Flow approach, which attempts to reconstruct individually each particle in the event, prior to the jet clustering, based on information from all relevant subdetectors.